Micro simulation to evaluate the impact of introducing pre-signals in traffic intersections - Vieira, António (2014)
The resolution of problems related to the saturation of traffic intersections usually consists in the construction of infrastructure such as bridges or tunnels. These represent the most costly type of solutions. As such, it becomes necessary to ponder other types of solution, of lower cost. Thus, this paper intends to provide a way to significantly improve the performance of a traffic intersection, by using pre-signals, on its approaches. For this purpose, a traffic micro simulation model was developed, using Simio. The simulation experiments show that the implementation of pre-signals result in an increase of the intersection flow's upper ceiling in over 10%, a decrease in the average waiting time per vehicle in 1 minute and a decrease of the queues average size. In addition, it was also found that there is always gain in the space occupied by the queues, taking into consideration the space investment needed to implement pre-signals.